The impact of non‐surgical periodontal treatment on serum levels of long chain–polyunsaturated fatty acids: a pilot randomized clinical trial. (31st May 2013) - Martinez, G. L.; Koury, J. C.; Brito, F.; Fischer, R. G.; Gustafsson, A.; Figueredo, C. M.
<x xml:space="preserve">Abstract</x> Background and Objective Our group recently found higher levels of serum long chain–polyunsaturated fatty acids (LC‐PUFAs) in patients with chronic periodontitis compared to controls. However, the effect of periodontal treatment on LC‐PUFA serum levels has not been investigated. The primary aim of the present study was to investigate the impact of periodontal treatment on LC‐PUFA serum levels. A secondary aim was to assess the effect of dietary ω‐3 supplementation on clinical outcome. Material and Methods The test group was composed of 10 patients with generalized chronic periodontitis (mean age 44 ± 6.4 years) treated with scaling and root planing associated with 4 mo of ω‐3 supplementation eicosapetaenoic acid (EPA) plus docosahexaenoic acid (DHA), 3 g/d. The placebo group was composed of 11 patients (47.9 ± 10.5 years) that received scaling and root planing plus placebo. The periodontal examination included probing depth, clinical attachment level, bleeding on probing and visible plaque index. Docosapentaenoic acid (DPA), EPA, DHA and arachidonic acid (AA) were detected using gas chromatograph. Results In the placebo group, all LC‐PUFAs levels reduced significantly (DHA, DPA and AA, p = 0.004; EPA, p = 0.008). In the test group, only DPA and AA showed a significant reduction (p = 0.005). Moreover, a significant decrease in the ratios AA/EPA and AA/DHA (p = 0.005) was observed in the test group. Conclusion Non‐surgical periodontal treatment reduced significantly the serum levels of all analyzed LC‐PUFAs except those presented in the supplementation. The ω‐3 dietary supplementation had no effect on clinical outcome of treatment.